Engaging Faculty and Students within Fully Online Asynchronous Academic Departments - jessica r nelson (Academic Chairpersons Conference Proceedings, 2016)
Presenter will discuss common barriers to implementing online programs including challenges of hiring distance faculty, communication breakdown between faculty and students, and issues with academic integrity. Best practices will be presented in order to help chairpersons overcome barriers to the online learning environment and engage both faculty and students with the use of innovation and inexpensive uses of telerobics, telecommunications software and enhancing their own universities learning platforms.
Keywords: Online learning; online faculty; telerobotics; best practices of online learning; technology